Formaldehyde and acetaldehyde emissions from residential wood combustion in Portugal - Cerqueira, Mário; Gomes, Luís; Tarelho, Luís; Pio, Casimiro (Atmospheric Environment, 2013)
A series of experiments were conducted to characterize formaldehyde and acetaldehyde emissions from residential combustion of common wood species growing in Portugal. Five types of wood were investigated: maritime pine (Pinus pinaster), eucalyptus (Eucalyptus globulus), cork oak (Quercus suber), holm oak (Quercus rotundifolia) and pyrenean oak (Quercus pyrenaica). Laboratory experiments were performed with a typical wood stove used for domestic heating in Portugal and operating under realistic home conditions. Aldehydes were sampled from diluted combustion flue gas using silica cartridges coated with 2,4-dinitrophenylhydrazine and analyzed by high performance liquid chromatography with diode array detection. The average formaldehyde to acetaldehyde concentration ratio (molar basis) in the stove flue gas was in the range of 2.1–2.9. Among the tested wood types, pyrenean oak produced the highest emissions for both formaldehyde and acetaldehyde: 1772 ± 649 and 1110 ± 454 mg kg−1 biomass burned (dry basis), respectively. By contrast, maritime pine produced the lowest emissions: 653 ± 151 and 371 ± 162 mg kg−1 biomass (dry basis) burned, respectively. Aldehydes were sampled separately during distinct periods of the holm oak wood combustion cycles. Significant variations in the flue gas concentrations were found, with higher values measured during the devolatilization stage than in the flaming and smoldering stages.
Keywords: Acetaldehyde; Biomass combustion; Emissions; Formaldehyde; Wood stove

Characterisation of PM10 emissions from woodstove combustion of common woods grown in Portugal - Gonçalves, Cátia; Alves, Célia; Evtyugina, Margarita; Mirante, Fátima; Pio, Casimiro; Caseiro, Alexandre; Schmidl, Christoph; Bauer, Heidi; Carvalho, Fernando (Atmospheric Environment, 2010)
A series of source tests was performed to evaluate the chemical composition of particle emissions from the woodstove combustion of four prevalent Portuguese species of woods: Pinus pinaster (maritime pine), Eucalyptus globulus (eucalyptus), Quercus suber (cork oak) and Acacia longifolia (golden wattle). Analyses included water-soluble ions, metals, radionuclides, organic and elemental carbon (OC and EC), humic-like substances (HULIS), cellulose and approximately l80 organic compounds. Particle (PM10) emission factors from eucalyptus and oak were higher than those from pine and acacia. The carbonaceous matter represented 44e63% of the particulate mass emitted during the combustion process, regardless of species burned. The major organic components of smoke particles, for all the wood species studied, with the exception of the golden wattle (0.07e1.9% w/w), were anhydrosugars (0.2e17% w/w). Conﬂicting with what was expected, only small amounts of cellulose were found in wood smoke. As for HULIS, average particle mass concentrations ranged from 1.5% to 3.0%. The golden wattle wood smoke presented much higher concentrations of ions and metal species than the emissions from the other wood types. The results of the analysis of radionuclides revealed that the 226 Ra was the naturally occurring radionuclide more enriched in PM10. The chromatographically resolved organics included n-alkanes, nalkenes, PAH, oxygenated PAH, n-alkanals, ketones, n-alkanols, terpenoids, triterpenoids, phenolic compounds, phytosterols, alcohols, n-alkanoic acids, n-di-acids, unsaturated acids and alkyl ester acids.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Biomass burning; Emissions; GC-MS; Organic tracers; PM10; Woodstove